Health Care Workers of Rawalpindi Medical University: The Vanguards at the COVID-19 War - Mohammad Mujeeb Khan, Mohammad Mujeeb Khan (Journal of Rawalpindi Medical College, 2020)
COVID-19 has been ravaging the world since November 2019, when the first case was detected. The population affected by this affliction is well North of 21 million cases worldwide. The hardest-hit countries include the USA (5.5 Million), Brazil (3.3 Million), and India (2.6 Million), accounting for nearly 55% of all cases. No part of the world has been left untouched by the plague and at this point, daily cases seem to be only increasing, with more than 250,000 cases, being reported worldwide daily. Close to 775,000 individuals have fallen prey to this disease, with the daily death tally averaging north of 5000 cases.1 14.5 million people have recovered to date, demonstrating a closed case mortality rate of 5%